2007
DOI: 10.1158/0008-5472.can-07-0212
|View full text |Cite
|
Sign up to set email alerts
|

Serum High-Density Lipoprotein Cholesterol and Risk of Non-Hodgkin Lymphoma

Abstract: Lymphoma patients often exhibit abnormal lipid metabolism. Recent evidence, however, suggests that a decrease in circulating high-density lipoprotein cholesterol (HDL-C) may occur during lymphomagenesis, reflecting underlying etiology such as inflammation. We investigated the relationship between prediagnostic HDL-C and non-Hodgkin lymphoma (NHL) in the Alpha-Tocopherol Beta-Carotene Cancer Prevention Study cohort. At baseline, serum HDL-C and total cholesterol concentrations from fasting blood, information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 47 publications
(48 reference statements)
3
59
2
1
Order By: Relevance
“…In addition, an inverse relationship for NHL was observed in our study. Previous reports on cholesterol indicted that reverse causation may substantially contribute to the risk-lowering effect of high blood lipids (Rose and Shipley, 1980;Lim et al, 2007;Strasak et al, 2009). Our observation that STG concentrations were positively associated with kidney cancer incidence in men (data not shown) contrasts with a recently published meta-analysis on BMI and renal cancer risk (Renehan et al, 2008).…”
Section: Discussioncontrasting
confidence: 90%
“…In addition, an inverse relationship for NHL was observed in our study. Previous reports on cholesterol indicted that reverse causation may substantially contribute to the risk-lowering effect of high blood lipids (Rose and Shipley, 1980;Lim et al, 2007;Strasak et al, 2009). Our observation that STG concentrations were positively associated with kidney cancer incidence in men (data not shown) contrasts with a recently published meta-analysis on BMI and renal cancer risk (Renehan et al, 2008).…”
Section: Discussioncontrasting
confidence: 90%
“…Recent evidence suggests that chronic immuno-inflammatory cells involve in tumorigenesis and tumor progression (Baecklund et al, 2006; Smedby et al, 2006; Lim et al, 2007). Reducing serum HDL concentration leads to chronic inflammation because of its anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that serum high-density lipoprotein (HDL) is in relation to incident cancers especially breast cancer. These findings imply that HDL might play a major role in tumorigenesis and tumor progression (Lim et al, 2007; Li et al, 2016; Wang et al, 2016). However, an integrated indicator based on serum TC and HDL levels, which might be superior to reflect the correlation between hepatic damage and tumor stages, has not yet been reported in HCC.…”
Section: Introductionmentioning
confidence: 98%
“…An elevated risk of esophageal cancer and colon cancer was observed in people with high levels of TG [36,37], and hypercholesterolemia has been suggested as a risk factor for rectal cancer [36]. High serum CH and TG levels raised the risk of prostate cancer and low HDL levels were associated with breast cancer, lung cancer, and non-Hodgkin’s lymphoma [38-41]. …”
Section: Reviewmentioning
confidence: 99%